EFFECT OF RATIONS CONTENT OF DEGRADABLE PROTEIN AND BARLEY GRAIN (STARCH) IN MILK PRODUCTION , COMPONENTS AND SOME BIOCHEMICAL BLOOD PARAMETERS OF AWASSI EWES - Omar ALMallah (Mesopotamia Journal of Agriculture, 2019)
This study was conducted in Al-Rashidiya animal breeding station, using 32 Awassi ewes (3-5 yrs old) with average body weight of 66.59 kg with their single born lambs. The ewes were divided randomly into 4 groups, the first (T1) and second (T2) groups fed on rations consist of 35% barley and contained two levels of rumen degradable protein (RDP) 10 and 13 g/ MJ metabolizable energy. while barley grain raised to 62% in the ration of third and fourth groups (T3 and T4) to increase the starch ratio with observance of the same level of RDP 10 and 13 g/ MJ respectively , and all the rations were iso calorie. Results indicated that RDP and starch levels had no significant effect on milk yield which were 968 , 1067 , 1127 ,and 867 g/ day, milk composition and yield with exception milk urea concentration were decreased (p<0.05) in T3 11.67 mg/ dl as compared with T2 21.14 mg/ dl, also milk urea concentration was increased significantly with RDP increase from 10 to 13 g/ MJ , but decreased (p<0.05) with increasing starch level. Ammonia concentration in rumen liquor decreased (p<0.05) after 2hrs of feeding in T1 4.57 mmol/ dl as compared with to T2 6.34 , T3 6.53 and T4 6.46 mmol/ dl. It was noted that treatments had no significant effect on body weight change in ewes , average daily gain in lambs and also in blood metabolites with exception the significant decrease (p<0.05) in the concentration of triglyceride in T3 14.67 mg/ dl as compared to other treatments were 20.19, 22.91 and 24.35 mg/ dl , also the increase in RDP level led to significant increased (p<0.05) in triglyceride concentration.